A phase I/II trial of AT9283, a selective inhibitor of aurora kinase in children with relapsed or refractory acute leukemia: challenges to run early phase clinical trials for children with leukemia. Issue 6 (1st December 2016) - Vormoor, B.; Veal, G. J.; Griffin, M. J.; Boddy, A. V.; Irving, J.; Minto, L.; Case, M.; Banerji, U.; Swales, K. E.; Tall, J. R.; Moore, A. S.; Toguchi, M.; et al.
Abstract: Aurora kinases regulate mitosis and are commonly overexpressed in leukemia. This phase I/IIa study of AT9283, a multikinase inhibitor, was designed to identify maximal tolerated doses, safety, pharmacokinetics, and pharmacodynamic activity in children with relapsed/refractory acute leukemia. The trial suffered from poor recruitment and terminated early, therefore failing to identify its primary endpoints. AT9283 caused tolerable toxicity, but failed to show clinical responses. Future trials should be based on robust preclinical data that provide an indication of which patients may benefit from the experimental agent, and recruitment should be improved through international collaborations and early combination with established treatment strategies.